Genomic insights into population structure and adaptive variation of Pimelodus yuma and Pimelodus grosskopfii in the Magdalena-Cauca Basin - Hayler Edu Ibarra Arcila; Juan Aicardo Segura Caro; Edna Judith Márquez; Jose Gregorio Martinez (PLoS ONE, 2026)
The biodiversity of the Magdalena–Cauca Basin, Colombia’s main fluvial system, is under severe threat from anthropogenic activities, imperiling endemic fish species such as Pimelodus yuma and Pimelodus grosskopfii . Using a population genomic approach based on single nucleotide polymorphisms (SNPs), we analyzed 64 individuals of P. grosskopfii and 57 individuals of P. yuma collected across ~1,600 km of the Magdalena–Cauca Basin. We identified two coexisting genetic stocks in both species, maintained by restricted gene flow that is associated with adaptive divergence rather than geographic distribution. Selection pressures, likely linked to the basin’s bimodal hydrological regime, were detected as major drivers of genetic structure. Historical demographic reconstruction analyses indicate that stock 1 in both P. grosskopfii and P. yuma was established in the basin during the Late Miocene–Pliocene (~4.5–5.5 MYA), with P. grosskopfii exhibiting an early expansion followed by long-term stability up to the present, while P. yuma maintained a stable population size until a recent decline. Stock 2 in both species was established during the Early Pleistocene (~1.7–2.5 MYA), followed by expansion and stability in P. grosskopfii , and a stable population size followed by a contraction–recovery–expansion dynamic in P. yuma , suggesting long-term persistence of neutral/adaptive processes shaping these stocks. Each stock should be considered a Management and Adaptive Unit, highlighting the need for targeted conservation actions and broader strategies to ensure their persistence under ongoing environmental and anthropogenic pressures in the Magdalena–Cauca Basin.